Sprinting training, techniques and improving performance - Husbands, Chris (The Crowood Press Ltd, 2013)
Suitable for all athletes at the beginning or development stages of their sprint careers who are committed to running faster, this book covers various sprint events from 60metres to 400 metres, as well as the hurdles and relay; principles of biomechanics, limiting factors and potential areas of capability; and training and planning.